STRATEGI BERTAHAN DAN STRATEGI ADAPTASI PETANI SAMIN TERHADAP DUNIA LUAR (Petani Samin Di Kaki Pegunungan Kendeng Di Sukolilo Kabupaten Pati) - SUGIHARDJO SUGIHARDJO; ENY LESTARI; AGUNG WIBOWO (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2012)
Poor peasants who are very sensitive in economic domain, decreasing and harvest failure will cause againts to hold in livelihood. Subsisten morality and safety of peasants to yield risk and decrease probability of harvest. It is not maximize profit oriented. In that context, peasant have rejected market economic which were maximal profit oriented. Basically, rural community have to much local knowledge or local wisdom that are key to recognise socio cultural of community. This study in the first aimed: (1) to discribe how holding strategy of Samin community to face outsider; (2) to describe how adaptation strategy of Samin vcommunity for change.